Intercambios eruditos en la Inglaterra moderna: una carta de John Evelyn y la biblioteca de Samuel Pepys - Pawelkowski, Adriana; Burucúa, José E. (Cuadernos de Historia Moderna, 2006)
The start point of this article is a letter sent by John Evelyn to Samuel Pepys on August the 12th. 1689, in which Evelyn gives to his friend some opinions and advises about painted or engraved portraits, worth for being the ornament in a library. Sir John’s text deals also with the state of public and private libraries in England and it ends with the presentation of a project for a public library and an academy devoted to the improvement of the english language. The main ideas of Evelyn are related to: 1) the cultural models furnished by France and Italy to the english civilization at the end of the XVIIth. century; 2) the relationships between images and texts as a basic dialectics for the reading and aesthetic appropriation practices; 3) the persistency of the Bacon’s program at the Royal Society, considered in the huge sense of an historical organization of knowledge. The article analyzes too the influence of Evelyn’s ideas over the uses that Samuel Pepys gave to his own library. The conclusions deal with the peculiar role of Spain as a cultural model for diversion, with the complex, open-minded and fluid wisdom of the rising bourgeoisie in England at the second half of the XVIIth. century, with the multiplicity of cultural practices in a reader such as Pepys, and with the central position of the wavering between texts and images for all of them.